Messages of invasive Perccottus glenii individuals eaten by an Esox lucius from the Danube Delta - Telcean, Ilie-Cătălin; Cicort-Lucaciu, Alfred-Ştefan (Journal of Fisheries, 2016)
In the stomach of a pike from the Danube Delta we have found seven Perccottus glenii individuals. Their message indicated that in the Danube Delta P. glenii has already large population. Also, it proves that in its habitats, the pike can consume numerous individuals of this invasive species. Their gut contents prove that P. glenii hunted near the shores, ingesting numerous terrestrial preys.